Analysis of the translation problems and techniques of the English - Spanish translation of four chapters of the book how to be somebody by Mark Mendes (2024)
This qualitative descriptive research analyzes the translation problems and the techniques used to solve them in the process of translating, from English into Spanish, four chapters of the Catholic book How to Be Somebody by Mark Mendes, belonging to the personal growth and spirituality genres and the instructional text typology. These types of studies constitute a communicative tool for foreign language learners and pre-service teachers since translation serves as a bridge between languages and cultures, combining theoretical bases with professional practices. Also, translation works are helpful for the development of language skills, awareness of the differences between languages and cultures, and the recognition of the communicative situation of texts. The translation was carried out from a functional perspective. It started with the identification of the genre and text typology of the source text (ST) to then perform a textual analysis based on Nord’s model (2005) to determine the Skopos (i.e., the purpose, function or aims of the text). Finally, the problems encountered and the techniques applied during the process were recorded and categorized following Nord’s (2005) translation problems classification (pragmatic, convention-related, linguistic, and text-specific problems) and Molina and Hurtado’s (2001) eighteen revised translation techniques. Problems of all four categories were found, and eight different translation techniques were applied to solve them (established equivalent, reduction, amplification, adaptation, modulation, literal translation, borrowing, and linguistic amplification). The results suggest a link between text genre/text typology and the type of translation problems encountered, as well as between translation problems and the techniques applied to solve them. Also, the sociocultural context of the ST and TT plays a fundamental role in the translator’s decision- making process when facing such problems.